SPIA Uganda Report 2025: Agricultural Diversity Under Stress - Ilukor, John; Letaa, Emmanuel; Khanal, Amit; Barros, Julio; Taye, Lemi; Gimode, Davis; Ponzini, Giulia; Asea, Godfrey; Ssennono, Vincent; Stevenson, James R.; Lybbert, Travis; Macours, Karen (2025)
SPIA Uganda Report 2025 – Agricultural Diversity Under Stress